Secure and Efficient Handover Authentication Based on Bilinear Pairing Functions - Daojing He; Chun Chen; Chan, Sammy; Jiajun Bu (IEEE transactions on wireless communications, 2012)
Seamless handover over multiple access points is highly desirable to mobile nodes, but ensuring security and efficiency of this process is challenging. This paper shows that prior handover authentication schemes incur high communication and computation costs, and are subject to a few security attacks. Further, a novel handover authentication protocol named PairHand is proposed. PairHand uses pairing-based cryptography to secure handover process and to achieve high efficiency. Also, an efficient batch signature verification scheme is incorporated into PairHand. Experiments using our implementation on laptop PCs show that PairHand is feasible in real applications.